Development of iron-base composite materials with high thermal conductivity for DEMO. Issue 1645 (2014) - Homma, H.; Hashimoto, N.; Ohnuki, S.
ABSTRACT: One of the critical issues for development of the nuclear fusion demonstration reactor (DEMO) is the high heat flux on heat-resistant equipments, especially the blanket and divertor. Materials of such equipments require relatively high thermal conductivities. In this study, we developed iron-based composite materials with carbon nanotube (CNT) and copper, which have high thermal diffusivities, by means of Hot Pressing (HP) and Spark Plasma Sintering (SPS). The thermal diffusivity in the iron/CNT composites was not high enough compared with that of pure iron, while iron/copper composite showed a relatively high thermal diffusivity in the joining conditions. One of the reasons not to be improved thermal diffusivity could be non-mono-dispersion of CNT by the formation of carbides in the matrix.